1986
DOI: 10.1007/bf00250519
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth temperature on the morphology and performance of Zymomonas mobilis ATCC 29 191 in batch and continuous culture

Abstract: Summary. Increasing the temperature in chemostat culture of Zymomonas mobilis ATCC 29 191 with low and high glucose concentrations was found to result in a decreasing frequency of septation leading to the formation of long filaments and in increasing outer membrane blebbing. Whether this effect is strain specific or universal in Zymomonas is, unknown. Improvements in the fermentation kinetics could be achieved at elevated temperatures, with an optimum at 33°C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Within the temperature range of 24–45 °C, cells gradually changed from a short rod shape to a filament shape as the temperature increased (Fig. 1 a, b), which was consistent with previous studies [ 20 , 27 ]. At the same time, the results of the flow cytometer were also consistent with those of the microscopic ones (Fig.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Within the temperature range of 24–45 °C, cells gradually changed from a short rod shape to a filament shape as the temperature increased (Fig. 1 a, b), which was consistent with previous studies [ 20 , 27 ]. At the same time, the results of the flow cytometer were also consistent with those of the microscopic ones (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Previous studies indicated that temperature affected the growth and ethanol production of Z. mobilis with biomass and ethanol production reduced at higher temperatures [ 14 , 18 , 19 ]. Temperature also affected the morphology of Z. mobilis , and the cell shape changed from short rods under optimal temperature to elongated filaments under high temperature, which is similar to the morphology under other stress conditions such as wood hydrolysate, molasses, urea or various salts [ 20 22 ]. Stevnsborg et al discovered that the shape of Z. mobilis cells returned to normal short rods from filaments when the culture temperature was reduced from 36 to 30 °C, and proposed that the arrest of septation and cell division was due to temperature-sensitive enzymes involved in septation [ 20 ].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Perhaps the greatest obstacle to commercialization is that, compared to yeast, much less practical experience exists for the Z. mobilis fermentation. The extensive work done in the field of evaluation and optimization of fermentation techniques (recent publications: [82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99]) reflects the neccessity for the development of Z. mobilis-specific processes, especially those that can operate stably in a non-sterile environment. The narrow range of substrates utilized by Z. mobilis (i.e., glucose, fructose and sucrose), the formation of by-products in fructose and sucrose-containing media and the low salt tolerance are disadvantageous for commercial applications.…”
Section: Discussionmentioning
confidence: 99%
“…This filamentous growth has already been reported in inhibitory conditions such as high temperature (Stevnsborg et al, 1986) or high salt concentration (StevnsborgandLatiord, 1986).Bycontrast, the mutant strain Cl07 showed a majority of rod shape cells. This result suggested that inhibition effects were less important with strain Cl07 than with strains ZM4 and SBE15.…”
Section: Methodsmentioning
confidence: 67%